THE CORRECTION OF ENDOTHELIAL DYSFUNCTION WITH THE HELP OF DISTANT ISCHEMIC AND PHARMACOLOGICAL PRECONDITIONING WITH THERMAL LOCAL ASPHYXIA OF KIDNEY - O. I. Bratchikov; M. V. Pokrovskiy; V. V. Elagin; D. A. Kostina (Вестник урологии, 2018)
This article contains the results of research of the endothelial dysfunction arising during the modeling of thermal local asphyxia of kidney and possibilities of their correction by distant ischemic and pharmacological preconditioning. The modeling of thermal local asphyxia of kidney is characterized by the disturbance of microcirculation and expression of eNOS in the kidney tissue. The usage of distant ischemic preconditioning and phosphodiesterase inhibitors type 5 sildenafil and tadalafil leads to pronounced correction of microcirculation dysfunction and activity of eNOS. During the modeling of thermal local asphyxia of kidney against endothelium dysfunction caused by ADMA-like L-NAME induced deficiency of nitric oxide more pronounced dysfunction of microcirculation and activity of eNOS are observed. The usage of distant ischemic and pharmacological preconditioning with the help of phosphodiesterase inhibitors type 5 in this type of pathology led to pronounced correction of microcirculation dysfunction and activity of eNOS. The injection of glibenclamide blocker of ATP – dependent K+ channels during the correction of the disturbance caused by the modeling of thermal local asphyxia of kidney with the help of distant ischemic and pharmacological preconditioning leads to the decrease of its efficiency.Disclosure: The study did not have sponsorship. The authors have declared no conflicts of interest.